Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.isci.2020.101262
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Tackles the Endoplasmic Reticulum: A First Genomic Study on a Titanium Anticancer Metallodrug

Abstract: PhenolaTi is an advanced non-toxic anticancer chemotherapy; this inert bis(phenolato)bis(alkoxo) Ti(IV) complex demonstrates the intriguing combination of high and wide efficacy with no detected toxicity in animals. Here we unravel the cellular pathways involved in its mechanism of action by a first genome study on Ti(IV)-treated cells, using an attuned RNA sequencing-based available technology. First, phenolaTi induced apoptosis and cell-cycle arrest at the G2/M phase in MCF7 cells. Second, the transcriptome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 88 publications
0
25
0
Order By: Relevance
“…109,110 26 initially exhibited a low fluorescence emission at 510 nm in PBS buffer (pH 7.4), and the sequential addition of H 2 O 2 and GSH was shown to afford TPP-NH 2 ArSO 3 H, a process initiated by Nearly 50% of cancer patients with solid tumours will receive platinum (Pt)-based therapy. 111 The Pt(II)-based therapeutics that have been approved to treat cancers include cisplatin, carboplatin, nedaplatin, oxaliplatin, and lobaplatin. Unfortunately, their poor tumour specificity leads to dose-limiting toxicities and a narrow therapeutic index, severely limiting their clinical efficacy.…”
Section: Prodrugs and Activatable Phototherapeutics Responsive To Eit...mentioning
confidence: 99%
See 1 more Smart Citation
“…109,110 26 initially exhibited a low fluorescence emission at 510 nm in PBS buffer (pH 7.4), and the sequential addition of H 2 O 2 and GSH was shown to afford TPP-NH 2 ArSO 3 H, a process initiated by Nearly 50% of cancer patients with solid tumours will receive platinum (Pt)-based therapy. 111 The Pt(II)-based therapeutics that have been approved to treat cancers include cisplatin, carboplatin, nedaplatin, oxaliplatin, and lobaplatin. Unfortunately, their poor tumour specificity leads to dose-limiting toxicities and a narrow therapeutic index, severely limiting their clinical efficacy.…”
Section: Prodrugs and Activatable Phototherapeutics Responsive To Eit...mentioning
confidence: 99%
“…Nearly 50% of cancer patients with solid tumours will receive platinum (Pt)-based therapy. 111 The Pt( ii )-based therapeutics that have been approved to treat cancers include cisplatin, carboplatin, nedaplatin, oxaliplatin, and lobaplatin. Unfortunately, their poor tumour specificity leads to dose-limiting toxicities and a narrow therapeutic index, severely limiting their clinical efficacy.…”
Section: Small-molecule Prodrugs and Activatable Phototherapeuticsmentioning
confidence: 99%
“…23 The exact mechanism of action of phenolaTi and related Ti(IV) complexes is still largely under investigations, with previous observations pointing to the participation of endoplasmic reticulum-(ER-) stress and hypoxia in tumor demise. [27][28][29][30] Several metal complexes have been shown to possess antibacterial activities. 31,32 In particular, it has been reported that Ti-based compounds inhibit the growth of Escherichia coli, Salmonella typhimurium, and Pseudomonas aeruginosa, 33 and TiO 2 nanoparticles generate reactive oxygen species which are lethal to bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The types of organic ligands in titanium-based complexes can alter their targets. ( Guo et al, 2000 ; Miller et al, 2020 ). Therefore, the ligand modification in metal-based complexes can significantly influence their engagement to different targets ( Meggers, 2007 ; Blanck et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%